Water exchange traded funds: A study on idiosyncratic risk using Markov switching analysis - Gurudeo Anand Tularam; Rajibur Reza (Cogent Economics & Finance, 2016)
We investigate the relationship between idiosyncratic risk and return among four water exchange traded funds-PowerShares Water Resources Portfolio, Power Shares Global Water, First Trust ISE Water Index Fund, and Guggenheim S&P Global Water Index ETF using the Markov switching model for the period 2007-2015. The generated transition probabilities in this paper show that there is a high and low probability of switching between Regimes 1 and 3, respectively. Moreover, we find that the idiosyncratic risk for most of the exchange traded funds move from low volatility (Regime 2) to very low volatility (Regime 1 and 3). Our study also identify that the beta coefficients are positive and entire values are less than 1. Thus, it seems that water investment has a lower systematic risk and a positive effect on the water exchange traded index funds returns during different regimes.
Keywords: 330; idiosyncratic risk; water investment; transition probabilities; Markov switching model; water exchange traded funds